2018
DOI: 10.1007/s40265-018-0894-6
|View full text |Cite|
|
Sign up to set email alerts
|

OnabotulinumtoxinA: A Review in the Prevention of Chronic Migraine

Abstract: An intramuscular formulation of onabotulinumtoxinA (onabotA; Botox®) is currently the only therapy specifically approved for the prevention of headaches in adults with chronic migraine (CM) in the EU and North America. This article provides a narrative review of relevant data on the drug in this indication from an EU perspective. OnabotA was originally approved on the basis of pooled data from two phase III studies (PREEMPT 1 and 2). In these pivotal studies, injection of up to five cycles of onabotA (155–195 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 60 publications
3
60
0
4
Order By: Relevance
“…The presence of migraines in 50% of our cases suggests that migraines may be a risk factor for the development of intractable postoperative HP. 13,14 Two large multicenter, controlled trials, PREEMPTs 1 and 2, demonstrated that onabotA therapy significantly decreased the frequency, duration, and severity of HA episodes in patients with chronic migraines, one-third of whom had failed to respond to greater than 3 oral prophylactic therapies. The overall presence of preoperative headache prior to developing POH was 32%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of migraines in 50% of our cases suggests that migraines may be a risk factor for the development of intractable postoperative HP. 13,14 Two large multicenter, controlled trials, PREEMPTs 1 and 2, demonstrated that onabotA therapy significantly decreased the frequency, duration, and severity of HA episodes in patients with chronic migraines, one-third of whom had failed to respond to greater than 3 oral prophylactic therapies. The overall presence of preoperative headache prior to developing POH was 32%.…”
Section: Discussionmentioning
confidence: 99%
“…Rimaaja et al echo this finding in that preoperative migraine was present in 77% of patients with preoperative headache who later developed POH after acoustic neuroma resection. 13,14 Its use in the treatment of other forms of HA is less established and many studies show no significant effect; however, a growing body of literature is now suggesting that botulinum toxin can be used for postsurgical pain. 19 In patients #1 and #2, surgical trauma may have aggravated their preexisting condition, as evidenced by the migrainous features of headaches in patient #2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations